Perfluorinated Ammonium and Phosphonium Ionic Liquids - Alpers, Torben; Muesmann, Thomas W. T.; Temme, Oliver; Christoffers, Jens (Synthesis, 2018)
Ammonium and phosphonium ionic liquids with perfluorinated side chains were prepared as hybrid materials for surface impregnation. Melting points of the triflimide salts range up to 95 °C. The key feature of this investigation are relatively short perfluorohexyl residues as the fluorinated part of the cations, making the target compounds beneficial alternatives to established products because of their enhanced degradability and therefore lower bioaccumulativity. In the ammonium series, pyrrolidinium, piperidinium, morpholinium triflimides as well as the dication derived from DABCO were prepared. Mono-phosphonium triflimides were obtained from triphenyl- and diphenylphosphane. Diphosphonium bistriflimides were obtained from bis(diphenylphosphano)alkanes, Ph2P(CH2)nPPh2 with n = 2–5. As alkylating reagents, n-C6F13CH2CH2OTf and n-C6F13CH2CH2I were applied.
Keywords: ionic liquids; fluorine compounds; phosphorus compounds; ammonium salts; phosphonium salts; triflimide